Holothuria (Lessonothuria) insignis Ludwig, 1875 (formally resurrected from synonymy of H. pardalis Selenka, 1867) and Holothuria (Lessonothuria) lineata Ludwig, 1875—new additions to the sea cucumber fauna of Pakistan, with a key to the subgenus Lessonothuria Deichmann (Echinodermata: Holothuroidea) - Ahmed, Quratulan; Thandar, Ahmed S.; Ali, Qadeer Mohammad (Zootaxa, 2020)
Two specimens of a species herein identified as Holothuria (Lessonothuria) insignis Ludwig, 1875 and a single specimen identified as Holothuria (Lessonothuria) lineata Ludwig, 1875, were collected from the intertidal zone at low tide from two coastal localities in Karachi (Buleji and Sunahri). This paper briefly documents their morphology and habitat characteristics and formally resurrects H. (L.) insignis from the synonymy of H. (L.) pardalis Selenka, 1867, based on the observations of the ossicles assemblage deduced from current material, syntype, some material at the NHMUK (Natural History Museum,UK), and literature. H. pardalis is also commented on and compared with its related congeners in Pakistan, in tabular form. A key is presented of all species of the Lessonothuria group currently recognized in WoRMS.